You are on page 1of 3

# Math 55

## 1. Determine if the following sequence/series converges or diverges.


ln(1 + en )

(a)
n n=1
ln(1 + en ) en en
Solution. lim = lim = lim = 1.
n n n 1 + en n en
Therefore the sequence is convergent.

X ln(1 + en )
(b)
n
n=1
ln(1 + en )
Solution. Since lim = 1 6= 0, the series diverges by Divergence Test.
n n

X (1)n
(c)
ln(n + 1)
n=1
1
Solution. Let bn = .
ln(n + 1)
1
i. lim bn = lim =0
n n ln(n + 1)
1 1
ii. bn+1 = < = bn , so {bn } is decreasing
ln(n + 2) ln(n + 1)
Therefore, the series converges by the Alternating Series Test.

2n 5n
X 
(d)
n+1
n=1
2n 5n

Solution. Let an = .
n+1
 1
1
2n 5n n 
2n 5

lim |an | = lim = lim = 25 > 1.
n

n n n + 1 n n + 1

## Therefore the series diverges by Root Test.

X n5 + n4
(e)
n7 + n3 n + 1
n=1
n5 + n4 n5 1
Solution. Let an = and bn = 7 = 2 .
n73
+n n+1 n n
an n5 + n4 n7 + n6
lim = lim 7 3
n2 = lim 7 =1>0
n bn n n + n n + 1 n n + n3 n + 1

X 1 X n5 + n4
Since is convergent (p-series with p = 2 > 1), the series also converges by
n2 n7 + n3 n + 1
n=1 n=1
Limit Comparison Test.

X 2
2. Evaluate the sum by looking at its nth partial sum.
n2 1
n=2
n
X 2
Solution. Let sn = . By partial fraction decomposition,
i2 1
i=2

n  
X 1 1
sn =
i1 i+1
i=2
           
1 1 1 1 1 1 1 1 1 1 1
= 1 + + + + ... + +
3 2 4 3 5 4 6 n2 n n1 n+1
1 1 1
= 1+
2 n n1
 
X 2 1 1 1 3
Hence, 2
= lim sn = lim 1 + = .
n 1 n n 2 n n1 2
n=2

X (x 2)n
3. Detrmine the radius of convergence and interval of convergence of the power series .
3n (n + 1)
n=0
(x 2)n
Solution. Let an = n . By Ratio Test,
3 (n + 1)
(x 2)n+1 3n (n + 1)
 
an+1 n + 1 x 2 |x 2|
lim = lim n+1
= lim =
n an n 3 (n + 2) (x 2)n n n + 2 3 3
|x 2|
The series converges when < 1, i.e., |x 2| < 3.
3
Hence, R = 3 and the series converges when 3 < x 2 < 3, i.e., on the interval (1, 5).

X (3)n X (1)n 3n X (1)n
If x = 1, the series becomes = = .
3n (n + 1) 3n (n + 1) n+1
n=0 n=0 n=0
1
Let bn = .
n+1
1
i. lim bn = lim =0
n n n + 1
1 1
ii. bn+1 = < = bn so {bn } is decreasing
n+2 n+1
Hence the series converges by Alternating Series Test.

X 3n X 1
If x = 5, the series becomes n
= .
3 (n + 1) n+1
n=0 n=0
1 1
Let an = and bn = .
n+1 n
an n
Then lim = lim = 1 > 0.
n bn n n + 1

X 1 X 1
Since diverges, also diverges by Limit Comparison Test.
n n+1
n=1 n=1

## Hence, the interval of convergence is [1, 5).

1
4. Find a power series representation for ln 1 + 2x using the power series reprentation for .
(1 + 2x)

1 1
Solution. First, notice that dx = ln(1 + 2x) + c = ln 1 + 2x + c.
1 + 2x 2
1
Now, we obtain a power series for :
1 + 2x

1 1 X X
= = (2x)n = (2)n xn
1 + 2x 1 (2x)
n=0 n=0

Therefore,

1 X X (2)n xn+1
ln 1 + 2x = dx = (2)n xn dx = +C
1 + 2x n+1
n=0 n=0

X (2)n xn+1
Letting x = 0, we get C = ln 1 = 0. Hence, ln 1 + 2x = .
n+1
n=0

X (2 ln 2)n
5. Find the Maclaurin series for f (x) = e2x and use this to find the sum .
n!
n=1

X xn
Since ex = , we have
n!
n=0

2x
X (2x)n X 2n
e = = xn
n! n!
n=0 n=0

Letting x = ln 2, we obtain

X 2n
e2 ln 2 = (ln 2)n
n!
n=0

2
X (2 ln 2)n
eln 2 =
n!
n=0

X (2 ln 2)n 2
Hence, = eln 2 = 4.
n!
n=0

6. Find the third degree Taylor polynomial for f (x) = ln(1 + x) centered at 0 and use it to approximate ln(1.5).

f (0) = ln 1 = 0
f 0 (x)= (1 + x)1 f 0 (0) = 1
f 00 (x) = (1 + x)2 f 00 (0) = 1
f 000 (x) = 2(1 + x)3 f 000 (0) = 2
3
X f (i) (0) x x2 2x3
Therfore, T3 (x) = xi = 0 + + .
i! 1! 2! 3!
i=0
 
1 1 1 2 1 1 1 10
Hence, ln(1.5) T3 = 2 + 3 = + = .
2 2 2 2 2 3! 2 8 24 24